EVALUASI DAN OPTIMASI KEMAMPUAN KINERJA STRUKTUR BAJA DENGAN ANALISIS PUSHOVER MENGGUNAKAN PROGRAM SAP2000 - Davin Pradipta Davin; Niken Warastuti (Jurnal Infrastruktur, 2019)
Indonesia is a country which is in an earthquake prone area. Earthquake disasters are destructive natural phenomena. The damage caused is very large, especially in the field of steel structures of buildings. The effect of earthquakes is an important factor to planning the design of building structures. Existing buildings are claimed to be earthquake resistant by planners, but not necessarily the results as expected. Along with the development of technological advances in the field of civil engineering, new concepts and methods emerged in the analysis and planning of earthquake resistant buildings, one of which was the concept of Performance Based Seismic Evaluation (PBSE) with static thrust load analysis or Pushover analysis. This method is able to provide information on the pattern of collapse of buildings that exist when burdened with earthquake forces that exceed the capacity of the building, whether direct collapse or building is capable of behaving nonlinear (progressive) before total collapse occurs. The purpose of the final assignment is to evaluate and optimize the performance of the load on the factory building to determine the effective capacity of the structure and behavior by showing the scheme of plastic joints on the beam and column elements with the Pushover method based on the Applied Technology Council (ATC-40) code and determining the level structural performance of earthquake prisoners based on the code. From the results of the study, it was found that the performance point is V = 61.027 Ton and D = 0.074 m. The structure of the building is able to provide nonlinear behavior that is indicated by the initial phase and the majority of the occurrence of plastic joints occurs in the beam element and then the column element. Structural performance levels are included in the Immediate Occupancy criteria, which means that minor structural damage occurs and the building can be reused immediately again.